Gema Bilah Kaca: Bentuk Inovasi Gamelan Sebagai Upaya Pelestarian Budaya di Kabupaten Pacitan - Ipuk Widyastuti (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2022)
The purpose of this paper is to provide an explanation of the process of making glass gamelan which has recently become a topic of discussion among musicians of the musical arts. Musical art is an intangible form of heritage from historical civilization in the form of chanting music originating from gamelan. In general, gamelan is made of bronze, iron, or brass. So it is different with the gamelan in Song Meri Studio, this studio tries to innovate by introducing gamelan made of glass. This study uses a descriptive analysis method by describing the data from research conducted through field observations, interviews, and collection of video samples uploaded to the You Tube channel. The sample in this study is the Song Meri Studio located in Sukoharjo, Pacitan. The findings show that the birth of the glass gamelan has shattered the enthusiasm of the people in the Nitikan area, Sukoharjo, Pacitan to continue to perform in the midst of the incessant pandemic. By utilizing glass waste as a raw material for making gamelan, Sanggar Song Meri succeeded in attracting public interest and even the regent of Pacitan was inspired to continue to preserve culture even with limited tools. In short, the results of the research that to obtain high and low notes, the effort that can be done is to adjust the length and width of the glass blades, this is of course very different from the way of tuning gamelan within or copper in general.